Diversity in special education - Klugerová, Jarmila (Kultura-Społeczeństwo-Edukacja, 2020)
Klugerová Jarmila, Diversity in special education, Culture– Society – Education no 2(16) 2019, Poznań 2019, pp. 45–54, Adam Mickiewicz University Press. ISSN2300-0422. DOI 10.14746/kse.2019.16.3. The article discusses the programme of special education and its range of sub-fields. The introductory section summarises reflections on the origin of the field, philosophy and its formation, aims and target groups, paradigm shift and introduction of new methods and forms of pedagogical work in special education. The second part presents a new course Resocialisation and Prison Education in special education, which is one of the specialisations, pillars or schools of special education.